2023
DOI: 10.3390/w15152774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blade Exit Angle on the Performance and Internal Flow Pattern of a High-Speed Electric Submersible Pump

Chen Han,
Junze Liu,
Yang Yang
et al.

Abstract: The impeller vane exit placement angle has a critical role in the flow characteristics of the fluid inside the lobe, thus having a profound effect on the overall pump performance. The purpose of this study is to investigate the effect of the impeller exit angle on the operating characteristics of a high-speed well submersible pump, and the numerical calculation results of the original model are in good agreement with the experimental results. In this paper, five different impeller vane exit angles, namely 10°,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Given the obtained results, a significant increase in the head was achieved from 14.75 m of the basic stage to 65.04 m of the developed stage (model 04) of the pump, which is 440% more. Thus, the pump head, which is created by the flowing part with a basic stage (eight pieces), can be provided by a pump using only two designed stages (model 04) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Given the obtained results, a significant increase in the head was achieved from 14.75 m of the basic stage to 65.04 m of the developed stage (model 04) of the pump, which is 440% more. Thus, the pump head, which is created by the flowing part with a basic stage (eight pieces), can be provided by a pump using only two designed stages (model 04) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al [30] investigated the influence of impeller gap drainage width on the performance of a low-specific-speed centrifugal pump, and the results revealed that using a smaller gap width could significantly improve the performance. Han et al [31] presented the influence of various impeller blade outlet angles on the performance of a high-speed ESP using experimental and computational methods. It was found that the impeller vane exit angle had a significant effect on the pump performance curve.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [30] investigated the influence of impeller gap drainage width on the performance of a low-specific-speed centrifugal pump, and the results revealed that using a smaller gap width could significantly improve the performance. Han et al [31] presented the influence of various impeller blade outlet angles on the performance of a high-speed ESP using experimental and computational methods. It was found that the impeller vane exit angle had a significant effect on the pump performance curve.…”
Section: Introductionmentioning
confidence: 99%